A mesoscopic approach of the quench cracking phenomenon influenced by chemical inhomogeneities. (August 2017) - Said Schicchi, Diego; Hoffmann, Franz; Frerichs, Friedhelm
Abstract: Heat treatment simulation can be an effective tool aimed at solving failure problems economically. However, the quality of numerical predictions depend on the quality of the applied models. It is well know that during quenching cracks may form due to high localized stresses and strains fields generated within the component, but also residual states can cause in-service failures after treatment. In spite of the models improvements made in the field, a current limitation is the common assumption of homogeneous microstructures. Chemical (and consequently, structural) inhomogeneities are normally neglected. In this work, gas quenching tests on cylindrical specimens of 100Cr6 (SAE 52100) steel are proposed to experimentally investigate the microcrack generation. Metallographic, spectrometry and microprobe measurements are performed aimed at characterizing both inclusions (carbides) and segregation bands (carbon, chromium and manganese distribution). A finite element based model is proposed to numerically evaluate the criticality of the quenching process in a two stage approach. Firstly, the gas quenching problem is solved, in direct correspondence with the experimental tests performed. Afterward, the mesoscale response is studied in a representative volume element based approach. The mesoscopic geometries are generated based on experimental determinations of the carbides and segregations' distributions. The extended finite element method is used to account for the fracture initiation. The influence of carbides (size and content) and chemical segregations on the mesoscale failure/criticality response is numerically analyzed. The numerical approach here presented is proposed as a failure prediction methodology specifically focused on quench cracking taking into account real steel meso-geometries. Highlights: Mesoscale failure behavior of a bearing steel during quenching is studied. The XFEM is used to model the fracture behavior. Carbides and segregation bands are explicitly considered in a RVE based approach. A failure prevention criterion is defined considering chemical inhomogeneities. Gas quenching tests and simulations are conducted. Post-processing of EMPA results solved the problem of calculating Ms for this kind of steel.